2020
DOI: 10.1111/codi.15403
|View full text |Cite
|
Sign up to set email alerts
|

Segmental versus extended colectomy for tumours of the transverse colon: a systematic review and meta‐analysis

Abstract: There is no consensus on the appropriate extent of oncological resection for tumours of the transverse colon. Concerns regarding tumour factors such as pattern of lymph node spread and technical factors such as anastomotic perfusion lead to a variety of procedures being performed. Operations such as sub-total colectomy, extended right hemicolectomy, left hemicolectomy, transverse colectomy and segmental resection are all frequently performed for tumours of similar location [1-5].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Extended transverse colon surgery, such as extended right or left hemicolectomy, or segmental resection, such as transverse colectomy, can be performed in transverse colon cancer. A meta-analysis using seven comparative series compared the outcomes of extended and segmental resection [ 8 ]. Segmental resection had better outcomes about operating time and postoperative ileus.…”
Section: General Consideration Of Surgery For Transverse Colon Cancermentioning
confidence: 99%
“…Extended transverse colon surgery, such as extended right or left hemicolectomy, or segmental resection, such as transverse colectomy, can be performed in transverse colon cancer. A meta-analysis using seven comparative series compared the outcomes of extended and segmental resection [ 8 ]. Segmental resection had better outcomes about operating time and postoperative ileus.…”
Section: General Consideration Of Surgery For Transverse Colon Cancermentioning
confidence: 99%
“…In addition, the extended longitudinal resection margin should be broadly secured because the hepatic or splenic flexure area has dual lymphatic drainage. However, many studies have shown that there is no significant difference in the therapeutic effects of conventional radical resection and extended radical resection in colon cancer surgery [67][68][69][70].…”
Section: Longitudinal Resection Marginmentioning
confidence: 99%
“…Аналогичные результаты отмечены в работе S. Morarasu и соавт. [25], однако [35][36][37]. Исходя из выводов другой работы, метастазы в ЛУ вдоль средних ободочных сосудов локализовались в единичных случаях [38], однако в это исследование вошли пациенты с разными стадиями заболевания, включая случаи отдаленного метастазирования.…”
Section: вариация применяемых хирургических методикunclassified